Comprehension of HIV/AIDS Print Material among - Birir, Lilian Atieno Gangla (My University, 2011)
This research report describes a study which seeks to establish whether public information print material on HIV/AIDS is easily comprehensible to Adult Basic Education and Training Students. The study focuses on the visual presentations in the print material and seeks to establish whether these visual elements are effective as communication tools and if there are differences in the ways in which humans and objects are recognized and interpreted. The research material consists of thirty visuals which are taken from the HIV and AIDS and Treatment booklet. The recognition of humans, analogous objects and abstract objects and comprehension of the basic message were tested. Thirty individual interviews were carried out among Adult Basic Education and Training students. All respondents were presented with the thirty visuals in order to find out if they were able recognise the visual elements and if they were able to comprehend the intended message of the visual. The results indicate that visuals are useful as a communication tool on health issues with low literate audiences. Furthermore, the use of concrete representation of humans and analogous objects are easily understood by low literate readers. However, the use of abstract objects in print material makes it more difficult for the low literate reader to understand the message as the meaning of most abstract objects need to be learnt. Therefore, such health information documents which are targeted at the public should incorporate concrete visual elements such as humans and familiar objects as well as portray objects in the same manner in which they exist in the readers setting. Moreover, the use of abstract objects should be avoided because low literate readers may not have developed a high level of visual literacy.
MM - P&DM
Keywords: HIV/AIDS training material; Adult Basic Education and Training; Literacy; Health